(−)-Guaiol regulates autophagic cell death depending on mTOR signaling in NSCLC. Issue 8 (3rd August 2018) - Yang, Xiaohui; Zhu, Jiabei; Wu, Jianchun; Huang, Nan; Cui, Zhongqi; Luo, Yingbin; Sun, Fenyong; Pan, Qiuhui; Li, Yan; Yang, Qingyuan
ABSTRACT: (−)-Guaiol, a sesquiterpene alcohol with the guaiane skeleton, has been found in many Chinese medicinal plants and been reported to comprise various guaiane natural products that are well known for their antibacterial activities. Previously, we have shown its antitumor activity by inducing autophagy in NSCLC cells. However, its potential mechanism in inducing autophagy is still under our investigation. Here, data from our western blotting assays showed that, in NSCLC cells, (−)-Guaiol significantly blocked the mTORC2-AKT signaling by suppressing mTOR phosphorylation at serine 2481 (S2481) to induce autophagy, illustrated by the increasing ratio of LC3II/I. Besides, it impaired the mTORC1 signaling by inhibiting the activity of its downstream factors, such as 4E-BP1 and p70 S6K, all of which could obviously rescued by the mTOR activator MHY1485. Afterwards, results from biofunctional assays, including cell survival analysis, colony formation assays and flow cytometry assays, suggested that (−)-Guaiol triggered autophagic cell death by targeting both mTORC1 and mTORC2 signaling pathways. In summary, our studies showed that (−)-Guaiol inhibited the proliferation of NSCLC cells by specifically targeting mTOR signaling pathways, including both mTORC1 and mTORC2 signaling, providing a better therapeutic option for substituting rapamycin in treating NSCLC patients.